Digital Competency Crisis amid Rapid Disruption: A Critical Study of Islamic Religious Education Teachers’ Resistance for Learning Quality - Ahmad Syauqi 'Alaikar Rohman; Hasan Baharun (Universitas Nurul Jadid, 2025)
This study aims to critically examine the digital competency crisis among Islamic Religious Education (PAI) teachers, identify the factors underlying their resistance to digital transformation, and analyze its implications for learning quality. The rapid advancement of digital transformation has fundamentally reshaped educational practices; however, many teachers remain insufficiently prepared to adapt to these changes. PAI teachers face more complex challenges as they are required not only to master digital technologies but also to integrate them with Islamic values within the learning process. This study employed a qualitative approach using a library research design by reviewing reputable scholarly articles, international institutional reports, and relevant academic documents. Data were analyzed through content analysis, involving processes of data reduction, thematic categorization, conceptual synthesis, and critical interpretation. The findings reveal that the digital competency crisis among PAI teachers is not merely a matter of technical limitations but is also shaped by pedagogical, psychological, cultural, and institutional factors that contribute to resistance toward digital transformation. This resistance, in turn, reduces instructional innovation, limits meaningful technology integration, and weakens the relevance of Islamic Religious Education to the learning characteristics of the digital generation. Furthermore, the study highlights the urgency of developing a comprehensive and integrative framework to address this issue. Therefore, this study proposes a digital competency transformation model encompassing technical, pedagogical, epistemological, and ethical-spiritual dimensions as a strategic framework for enhancing the quality and relevance of Islamic Religious Education in the era of technological disruption.